Penguatan Aswaja An-Nahdliyah Berbasis Qanun Asasi KH. Hasyim Asy’ari Pada Diklat Gerakan Pemuda Ansor Kecamatan Pungging - Ahmad Muzakki Al Mahbubi; Imron Arifin; pengelola, pengelola (STAI Ihyaul Ulum Gresik, 2023)
The planting of Aswaja in the GP Ansor Training and Training is a program of the GP Ansor Leadership of Pungging Branch Children which is given to all its members. With their young age, all members of the GP Ansor, Head of the Pungging Branch, are expected to become people with good moral character. The focus of this research is the points in the Qanun Asasi, strategies for strengthening and implementing aswaja an nahdliyyah based on the Qanun Asasi KH Hasyim Asy'ari in the Ansor youth movement training, Pungging sub-district. This type of research is field research which is used to obtain the data needed to study how to strengthen Aswaja An-nahdliyah based on Qanun Asasi in the Ansor youth movement training in Pungging District. The results of this research are that: (1) The points in Qanun Asasi in chapter xii article 31 explain that Muslims have the right and obligation to receive Islamic education and teaching facilities. (2) Strategy for planting Aswaja by spreading the wings of organizations based on aswaja and nahdliyah and holding formal and non-formal activities such as training, prayers and pilgrimages. Ansor cadres who are involved in educational institutions also use the same strategy by inviting students to pray, do dhikr and include Aswaja lessons. (3) Strengthening the planting of aswaja is carried out by means of training, rakerancab, shalawat, dhikr and pilgrimage.